2011
DOI: 10.1007/s00414-011-0562-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of forces required for stabbing with screwdrivers and other blunter instruments

Abstract: In the UK, stabbing is the most common cause of homicide. The weapons used include knives, swords, screwdrivers and glass shards. Quantifying the exact force used in a stabbing incident is considered to be a difficult area due to the large number of variables present, such as sharpness of weapon, angle of attack and relative movements of the people involved. Having quantifiable data would allow a forensic pathologist to make a more informed decision when it comes to answering the commonly posed question in cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
(33 reference statements)
2
31
0
Order By: Relevance
“…Parmar et al [9] found that porcine skin, despite being slightly thicker due to its increased collagen density, has similar mechanical properties to human skin. When compared to other animal models (dogs and rats) the response of the porcine skin was the closest to that of human skin [10].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Parmar et al [9] found that porcine skin, despite being slightly thicker due to its increased collagen density, has similar mechanical properties to human skin. When compared to other animal models (dogs and rats) the response of the porcine skin was the closest to that of human skin [10].…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have identified that human skin's mechanical behavior is dependent on a variety of factors, such as age, gender, health and weight of the donor, as well as the location of the site and its orientation [1,2,[4][5][6][7][8]. The use of human skin in test situations may potentially make it difficult to analyze any experimental results and repeating of the experiment would be problematic [9]. A small number of studies [9][10][11] have used animal skin as an alternative but similarly its organic properties make results difficult to replicate.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This places serious doubt over the validity of 'walk-on' style defenses where such non-blade implements have been used. Recently, [25] have quantified the penetration force for other implements such as screwdrivers using silicone gel and related the cross-sectional area of the screwdriver head to the penetration force. Here, we have identified three characteristic dimensions of a blade which affect the penetration force.…”
Section: -20n Present Resultsmentioning
confidence: 99%